Carbon fiber composite material and its manufacturing method

By adding a specific range of carbon nanotubes and carbon black to the crosslinked fluoroelastomer and using the unrolling roll method to manufacture carbon fiber composites to form a multi-continuous structure, the problem of insufficient mechanical properties and permanent compression deformation performance of existing carbon fiber composites in high temperature environments is solved, and efficient mechanical properties and low deformation characteristics are achieved.

JP7654532B2Active Publication Date: 2025-04-01ASTEMO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021196787
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-12-03
Publication Date
2025-04-01
Estimated Expiration
2041-12-03

AI Technical Summary

Technical Problem

Existing carbon fiber composite materials have good mechanical properties in high temperature environments, but their permanent compression and deformation performance is insufficient, making it difficult to meet the demand for high temperature durability in semiconductor and chemical products.

Method used

A crosslinked fluoroelastomer (FFKM) containing carbon nanotubes with an average diameter of 0.7 nm to 30 nm and carbon black with an average particle diameter of 100 nm to 300 nm as the substrate was used to manufacture a carbon fiber composite material by an unrolling roll method to form a multi-continuous structure to improve the mechanical properties and thermal stability of the material.

Benefits of technology

It realizes high mechanical properties and low permanent compression deformation of carbon fiber composite materials in high temperature environments, meeting the demand for high temperature durability in semiconductor and chemical products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007654532000004
    Figure 0007654532000004
  • Figure 0007654532000005
    Figure 0007654532000005
  • Figure 0007654532000006
    Figure 0007654532000006
Patent Text Reader

Abstract

To provide a carbon fiber composite material which is excellent in mechanical characteristics at a high temperature, and permanent compression set characteristics under a high temperature environment.SOLUTION: A carbon fiber composite material contains a carbon nanotube and carbon black in a crosslinked perfluoroelastomer. The blending amount of the carbon nanotube is 0.1 pts.mass or more and 3.5 pts.mass or less with respect to 100 pts.mass of the perfluoroelastomer. The blending amount of the carbon black is 15 pts.mass or more and 50 pts.mass or less with respect to 100 pts.mass of the perfluoroelastomer. In a cross section of the carbon fiber composite material, there are a plurality of continuous structures. The number of continuous structures per unit area in the cross section is 0.80 pieces / μm2 to 3.50 pieces / μm2. The maximum length of each of the continuous structures in the cross section is 10 nm or more and 1,000 nm or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a carbon fiber composite material and a method for producing the same. [Background technology]

[0002] In recent years, composite materials with improved mechanical strength using carbon nanotubes have been attracting attention. However, carbon nanotubes have a strong cohesive property and tend to form agglomerates, making it very difficult to use them as fibrous reinforcing materials in composite materials.

[0003] In response to this, a carbon fiber composite material has been proposed in which the elastomer molecules bond with the radicals at the ends of the carbon nanotubes during the process of kneading the carbon nanotubes into an elastomer, thereby weakening the cohesive force of the carbon nanotubes and compounding the carbon nanotubes in a defibrillated state (for example, Patent Document 1).

[0004] In addition, a sealing member using perfluoroelastomer (FFKM) as an elastomer for a carbon fiber composite material has been proposed, and a sealing member with excellent chemical resistance as well as high heat resistance has been proposed, which can be used in downhole equipment for exploring underground resources such as oil and natural gas (for example, Patent Document 2).

[0005] Furthermore, a carbon fiber composite material with excellent blister resistance has been proposed by improving a carbon fiber composite material using a perfluoroelastomer (FFKM) (Patent Document 3). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2005-97525 A [Patent Document 2] Patent No. 5816474 [Patent Document 3] Patent No. 6284394 Summary of the Invention [Problem to be solved by the invention]

[0007] In the fields of semiconductors and chemical products, processing temperatures are becoming higher, and there is a trend for rubber products, such as sealing materials for peripheral devices, used in these fields to have relatively high heat resistance. However, while conventional carbon fiber composite materials using perfluoroelastomers have excellent mechanical properties at high temperatures, their compression set properties in high-temperature environments do not meet the performance requirements for rubber products in these fields.

[0008] Therefore, an object of the present invention is to provide a carbon fiber composite material that is excellent in mechanical properties at high temperatures and in compression set properties in a high-temperature environment, and a method for producing the same. [Means for solving the problem]

[0009] The present invention has been made to solve at least some of the above problems, and can be realized in the following aspects or application examples.

[0010] [1] One embodiment of the carbon fiber composite material according to the present invention is A carbon fiber composite material containing carbon nanotubes with an average diameter of 0.7 nm to 30 nm and carbon black with an average particle diameter of 100 nm to 300 nm in a crosslinked perfluoroelastomer, The amount of the carbon nanotubes blended is 100 parts by mass of the perfluoroelastomer. 0.1 parts by mass or more and 3.5 parts by mass or less of the total weight of the the amount of carbon black is 15 parts by mass or more and 50 parts by mass or less based on 100 parts by mass of the perfluoroelastomer, the carbon fiber composite material has a plurality of continuous structures in which the distance between adjacent carbon nanotubes or the distance between the carbon nanotubes and the carbon black is 100 nm or less in a cross section thereof, The number of the continuous structures per unit area in the cross section is 0.80 / μm2 ~3.50 pieces / μm 2 and The continuous structure has a maximum length in the cross section of 10 nm or more and 1000 nm or less.

[0011] [2] In one embodiment of the carbon fiber composite material, The tensile strength measured in accordance with ASTM D1414, except for the 260°C environment, is 2.2 MPa or more, and the elongation at break is 60% or more. The compression set measured according to ASTM D395 at 260° C. for 168 hours at 25% compression can be less than 50%.

[0012] [3] In one embodiment of the carbon fiber composite material, The international rubber hardness (IRHD) measured in accordance with JIS K6253 may be 68 or more and 82 or less.

[0013] [4] One embodiment of the method for producing a carbon fiber composite material according to the present invention comprises: A first mixing step of kneading 100 parts by mass of a perfluoroelastomer before crosslinking with 0.1 parts by mass to 3.5 parts by mass of carbon nanotubes having an average diameter of 0.7 nm to 30 nm to obtain a first mixture; a first thin passing step in which the first mixture is put into an open roll having a roll gap set to more than 0 mm and 0.5 mm or less and a roll temperature set to 0 ° C. to 50 ° C., and thin-passed to obtain a second mixture; a second mixing step of kneading 15 parts by mass or more and 50 parts by mass or less of carbon black having an average particle size of 100 nm or more and 300 nm or less with the second mixture to obtain a third mixture; a second thin-threading step in which the third mixture is fed into an open roll having a roll gap set to more than 0 mm and not more than 0.5 mm and a roll temperature set to 0° C. to 50° C., and thin-threaded to obtain a carbon fiber composite material; Including, the carbon fiber composite material has a plurality of continuous structures in which the distance between adjacent carbon nanotubes or the distance between the carbon nanotubes and the carbon black is 100 nm or less in a cross section thereof, The number of the continuous structures per unit area in the cross section is 0.80 / μm 2 ~3.50 pieces / μm 2 and The continuous structure has a maximum length in the cross section of 10 nm or more and 1000 nm or less. [Brief description of the drawings]

[0014] [Figure 1] FIG. 2 is a schematic diagram illustrating a continuous structure in a cross section of a carbon fiber composite material. [Diagram 2] This is an SEM image of a tensile fracture surface of a carbon fiber composite material. [Diagram 3] This is an SEM image of a tensile fracture surface of a carbon fiber composite material to explain the continuous structure. [Figure 4] FIG. 4 is a schematic diagram illustrating the continuous structure in FIG. [Diagram 5] FIG. 1 is a diagram illustrating a method for producing a carbon fiber composite material. [Figure 6] FIG. 1 is a diagram illustrating a method for producing a carbon fiber composite material. [Figure 7] FIG. 1 is a diagram illustrating a method for producing a carbon fiber composite material. [Figure 8] FIG. 1 is a diagram illustrating a method for producing a carbon fiber composite material. [Figure 9] FIG. 1 is a diagram illustrating a method for producing a carbon fiber composite material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Preferred embodiments of the present invention will be described in detail below with reference to the drawings. Note that the embodiments described below do not unduly limit the contents of the present invention described in the claims. In addition, not all of the configurations described below are necessarily essential components of the present invention.

[0016] 1. Carbon fiber composite materials A carbon fiber composite material according to one embodiment of the present invention is a carbon fiber composite material containing carbon nanotubes having an average diameter of 0.7 nm to 30 nm and carbon black having an average particle size of 100 nm to 300 nm in a crosslinked perfluoroelastomer, the carbon nanotubes being mixed in an amount of 0.1 to 3.5 parts by mass relative to 100 parts by mass of the perfluoroelastomer, and the carbon black being mixed in an amount of 15 to 50 parts by mass relative to 100 parts by mass of the perfluoroelastomer, the carbon fiber composite material having a crosslinked perfluoroelastomer ... 2 ~3.50 pieces / μm 2 and the maximum length of the continuous structure in the cross section is 10 nm or more and 1000 nm or less.

[0017] The carbon fiber composite material may have an international rubber hardness (IRHD) measured in accordance with JIS K6253 of 68 or more and 82 or less, and may further be 70 or more and 80 or less. If the international rubber hardness is less than 68, the tensile strength at high temperatures is low, and if it exceeds 82, the compression set properties are reduced.

[0018] The carbon fiber composite material has excellent heat resistance. Here, the heat resistance can be evaluated as a mechanical property at high temperature, specifically, the tensile strength and the elongation at break in a tensile test at high temperature, for example, 260°C. The carbon fiber composite material can have a tensile strength of 2.2 MPa or more and an elongation at break of 60% or more, and can have a tensile strength of 2.5 MPa or more and 5.0 MPa or less and an elongation at break of 65% or more and 120% or less, as measured in accordance with ASTM D1414 except in a 260°C environment. If the tensile strength of the carbon fiber composite material is less than 2.2 MPa and the elongation at break is less than 60%, the durability of the rubber product tends to decrease when the carbon fiber composite material is used to manufacture a rubber product such as a sealing material. In addition, the carbon fiber composite material can have a compression set of less than 50% after being held at 260°C, 168 hours, and 25% compression, as measured in accordance with ASTM D395, and can have a compression set of 48% or less. If the compression set of a carbon fiber composite material is 50% or more, a sealing material made from the carbon fiber composite material will collapse at high temperatures, making it difficult to maintain sealing properties. A carbon fiber composite material with these properties can be obtained by blending a specified amount of carbon black in addition to a relatively small amount of defibrated carbon nanotubes, using the manufacturing method described below.

[0019] In carbon fiber composite materials, carbon nanotubes are dispersed throughout in an defibrated state. Carbon fiber composite materials do not contain agglomerates of carbon nanotubes, because agglomerates can become the starting point of breakage and lead to a decrease in mechanical strength.

[0020] 1.1.Continuous structure The inventors of the present invention performed measurements of carbon fiber composite materials using a scanning electron microscope. It was found that carbon fiber composite materials with excellent compression set properties under high temperature conditions have a common structural feature.

[0021] Therefore, the structural features of the carbon fiber composite material 50 will be described in detail with reference to Figures 1 to 4. The carbon fiber composite material 50 shown in Figures 1 to 4 is a sample of Example 3 which will be described later.

[0022] Fig. 1 is a schematic diagram illustrating the structure in an image 90 of a cross section of a carbon fiber composite material 50, Fig. 2 is an SEM image 90 of a tensile fracture surface of the carbon fiber composite material 50, Fig. 3 is an image 90 showing a continuous structure 84 in the image 90 of Fig. 2, and Fig. 4 is a schematic diagram illustrating the continuous structure 84 in Fig. 3. Note that the "cross section" may be a freeze fracture surface or a tensile fracture surface. Also, "SEM" is an abbreviation for Scanning Electron Microscope.

[0023] In Fig. 1, the carbon nanotubes 81 are shown as round black dots and the carbon black 82 is shown shaded to make it easier to understand the arrangement of the carbon nanotubes 81 and the carbon black 82 in the cross section of the carbon fiber composite material 50. Furthermore, the continuous structure 84 is shown as one continuous structure by connecting adjacent carbon nanotubes 81 that are 100 nm or less apart or adjacent carbon nanotubes 81 and carbon black 82 that are 100 nm or less apart with a straight dashed line. Therefore, it can be seen that there are five continuous structures 84 within the range of Fig. 1. The remaining portion is perfluoroelastomer 30.

[0024] FIG. 1 is an enlarged view of the area surrounded by the dashed line in FIG. 4. FIG. 4 is a view created to identify the continuous structures 84 based on the image 90 in FIG. 2 and to count the number of them. A specific identification and measurement procedure will be described. First, the carbon nanotubes 81 and the carbon black 82 in the image 90 in FIG. 2 are identified. In order to make it easier to measure the distance between the objects, as shown in FIG. 3, the carbon nanotubes 81 appearing in the cross section in FIG. 2 are marked with black dots, and the carbon black 82 is filled in (it is white in FIG. 3, but is colored). This processing may be performed using image processing software, or may be drawn using drawing software. The identification and measurement may be performed using FIG. 3 as it is, but in order to make it easier to understand, the image 90 before processing may be erased from FIG. 3, and only the black dots and the filled-in area may be left to obtain FIG. 4. Then, the distance L1 between the adjacent carbon nanotubes 81 or the distance L1 between the carbon nanotubes 81 and the carbon black 82 in FIG. 4 is measured. The part where the distance L1 is 100 nm or less is drawn with a dashed straight line to identify and show the continuous structure 84. 4, the number of continuous structures 84 can be counted to calculate the number per unit area, and the maximum length L2 of each continuous structure 84 can be measured. In these measurement processes, the carbon nanotubes 81 and the carbon black 82 may be identified by binarizing the image 90 using image processing software, or the measurement of the distance L1 may be automated using a personal computer.

[0025] 1 to 4 contains carbon nanotubes 81 having an average diameter of 0.7 nm or more and 30 nm or less, and carbon black 82 having an average particle size of 100 nm or more and 300 nm or less, in a crosslinked perfluoroelastomer 30. The carbon nanotubes 81 will be described later in the section "2.3. Carbon nanotubes," and the carbon black 82 will be described later in the section "2.2. Carbon black."

[0026] As shown in Figs. 1 to 4, the cross section of the carbon fiber composite material 50 has a plurality of continuous structures 84 in which the distance L1 between adjacent carbon nanotubes 81 or the distance L1 between the carbon nanotube 81 and the carbon black 82 is 100 nm or less. The distance L1 is the distance between adjacent carbon nanotubes 81 or between the carbon nanotube 81 and the carbon black 82 at the position where they are closest to each other. In Fig. 1, the portion shown as connecting the carbon nanotube 81 and the carbon black 82 with a dashed straight line is the continuous structure 84. In the continuous structure 84, a certain carbon nanotube 81 is adjacent to another carbon nanotube 81 or carbon black 82 at a distance L1 of 100 nm or less, or the adjacent structures are continuous. When the distance L1 is 100 nm or less, it is considered that an interaction occurs between adjacent carbon nanotubes 81 or between adjacent carbon nanotubes 81 and carbon black 82. Note that, since the interaction between the carbon blacks 82 is considered to be small, even if the distance between the carbon blacks 82 is 100 nm or less, they are not treated as part of the continuous structure 84.

[0027] The average value of the distance L1 in the continuous structure 84 can be 10 nm or more and less than 100 nm, and further, the average value of the distance L1 can be 10 nm to 95 nm. If the average value of the distance L1 is less than 10 nm, the flexibility of the carbon fiber composite material 50 decreases. If the average value of the distance L1 is 100 nm or more, the interaction between the carbon nanotubes 81 or between the carbon nanotubes 81 and the carbon black 82 decreases, and the reinforcing effect decreases. The distance L1 is measured on an image 90 of a scanning electron microscope.

[0028] The number of continuous structures 84 per unit area in the cross section of the carbon fiber composite material 50 is 0.80 pieces / μm 2 ~3.50 pieces / μm 2 Furthermore, the number of continuous structures 84 per unit area in the cross section of the carbon fiber composite material 50 is 1.10 pieces / μm 2 ~2.90 pieces / μm 2The number of continuous structures 84 can be determined by identifying the continuous structures 84 in the image 90 as shown in FIG. 4, counting the number of them, and calculating the number of continuous structures 84 per unit area (μm 2 When the amount of carbon nanotubes 81 and carbon black 82 added is small, the number of continuous structures 84 is 0.80 pieces / μm 2 If it is less than 3.50 pieces / μm, the reinforcing effect is significantly inferior. 2 If the amount of carbon nanotubes 81 and carbon black 82 added is large, the number of continuous structures 84 may exceed 0.80 pieces / μm. 2 If the number of pieces / μm is less than 3.50, the continuous structure 84 is considered to be in a largely developed state, and the compression set characteristics in a high temperature environment are reduced. 2 If the temperature exceeds this range, the carbon nanotubes 81 may partially aggregate, resulting in deterioration of the physical properties.

[0029] The maximum length L2 of the continuous structure 84 in the cross section of the carbon fiber composite material 50 is 10 nm or more and 1000 nm or less. Furthermore, the maximum length L2 of the continuous structure 84 in the cross section of the carbon fiber composite material 50 can be 30 nm or more and 900 nm or less. The maximum length L2 of the continuous structure 84 is obtained by identifying the continuous structure 84 in the image 90 as shown in FIG. 4 and measuring the maximum length L2 of each of them. The maximum length L2 is a linear distance, and can also be called the maximum diameter when the continuous structure 84 is considered as one mass. If the maximum length L2 is less than 10 nm, most of the continuous structure 84 is composed of a pair of carbon nanotubes 81, so that the physical properties are not improved. Also, if the maximum length L2 is 1000 nm or more, the continuous structure 84 develops too much, and the compression set properties in a high temperature environment are reduced.

[0030] It is presumed that the continuous structure 84 has a higher elastic modulus than the phase of only the perfluoroelastomer 30, and therefore behaves like a single structure within the carbon fiber composite material 50. Therefore, the continuous structure 84 bears the stress on the carbon fiber composite material 50, resulting in excellent tensile strength and elongation at high temperatures. It is considered that in the continuous structure 84, interactions occur due to the stress field between adjacent carbon nanotubes 81 or between the carbon nanotubes 81 and the carbon black 82. In addition, since a plurality of continuous structures 84 are independently scattered within the carbon fiber composite material 50, the perfluoroelastomer 30 is continuous, and thus flexibility is maintained during deformation.

[0031] 2.Raw materials Next, the raw materials constituting the carbon fiber composite material will be described.

[0032] 2.1. Perfluoroelastomer The perfluoroelastomer (FFKM) used in carbon fiber composite materials has a Mooney viscosity of ML (1+10) The temperature at 121° C. may be 30 to 80. When the Mooney viscosity of the perfluoroelastomer is within this range, the process of kneading with the carbon nanotubes is relatively easy.

[0033] The perfluoroelastomer used in the carbon fiber composite material may have a fluorine content of 72% or more. If the fluorine content of the perfluoroelastomer is in this range, it is preferable because it has excellent chemical resistance.

[0034] Examples of such perfluoroelastomers include tetrafluoroethylene (TFE) / perfluoroalkyl vinyl ether (PAVE) copolymers, and examples of the perfluoroalkyl vinyl ethers (PAVEs) that can be used here include perfluoromethoxy vinyl ether (PMOVE), perfluoromethyl vinyl ether (PMVE), perfluoroethyl vinyl ether (PEVE), perfluoropropyl vinyl ether (PPVE), and other similar compounds.

[0035] The perfluoroelastomer may be a peroxide crosslinked type, a triazine crosslinked type, or the like.

[0036] 2.2.Carbon black The carbon black used in carbon fiber composite materials has an average particle size of 100 nm to 300 nm. The average particle size of carbon black can be determined by observing the particle diameters of 2,000 or more basic constituent particles using a scanning electron microscope and taking the arithmetic average.

[0037] As such carbon black, for example, reinforcing carbon black such as FT or MT can be used. By using carbon black having a relatively large particle size, it is possible to maintain the flexibility of the carbon fiber composite material while improving the compression set characteristics. It is preferable that the carbon black is not high-structured, and for example, it is preferable that the DBP absorption amount (method A) is 20 cm 3 / 100g~65cm 3 / 100g. This is because the development of the structure leads to the development of a continuous structure. Carbon fiber composite materials can use MT grade carbon black.

[0038] The amount of carbon black in the carbon fiber composite material is 15 parts by mass or more and 50 parts by mass or less per 100 parts by mass of perfluoroelastomer. The amount of carbon black in the carbon fiber composite material can be 20 parts by mass or more and 45 parts by mass or less per 100 parts by mass of perfluoroelastomer. If the amount of carbon black is less than 15 parts by mass, the rubber hardness and physical properties are low, and the mechanical strength is low. If the amount of carbon black is more than 50 parts by mass, the rubber hardness is high, and the tensile strength and elongation at break at high temperatures are low.

[0039] 2.3.Carbon nanotubes The carbon nanotubes used in one embodiment of the present invention may have an average diameter (fiber diameter) of 0.7 nm to 30 nm, and may further be 2 nm to 20 nm. Such carbon nanotubes have a relatively small average diameter, so that they have a large specific surface area, which improves the surface reactivity with the perfluoroelastomer matrix, and tends to improve poor dispersion of the carbon nanotubes in the perfluoroelastomer. Carbon nanotubes with a diameter of 0.7 nm or more are commercially available, and can be used in a wide range of applications. If the average particle size is 0 nm or less, it has the effect of being excellent in tear fatigue property and abrasion resistance. The carbon nanotubes can be subjected to a known activation treatment in order to improve the reactivity of the surface with the perfluoroelastomer. The average diameter of the carbon nanotubes can be measured by observation with an electron microscope. In the detailed description of the present invention, the average diameter and average length of the carbon nanotubes can be obtained by measuring the diameter and length at 200 or more points from, for example, 5,000 times magnification images taken with an electron microscope (the magnification can be appropriately changed depending on the size of the carbon nanotubes) and calculating the arithmetic average value.

[0040] Carbon nanotubes are at least one of so-called multi-walled carbon nanotubes (MWCNTs) and single-walled carbon nanotubes (SWCNTs), which have a shape formed by rolling up one surface (graphene sheet) of carbon hexagonal mesh graphite into a cylindrical shape, and carbon materials partially having a carbon nanotube structure can also be used. Carbon nanotubes may include multi-walled carbon nanotubes and single-walled carbon nanotubes. In addition to the name carbon nanotubes, they may also be called graphite fibril nanotubes or vapor-grown carbon fibers.

[0041] Carbon nanotubes can be obtained by a vapor phase growth method. The vapor phase growth method is also called catalytic chemical vapor deposition (CCVD), and is a method of manufacturing unprocessed carbon nanotubes by pyrolyzing a gas such as a hydrocarbon in the presence of a metal catalyst in the vapor phase. To explain the vapor phase growth method in more detail, for example, an organic compound such as benzene or toluene is used as a raw material, and an organic transition metal compound such as ferrocene or nickelcene is used as a metal catalyst, and these are introduced into a reactor set at a high reaction temperature of, for example, 400°C to 1000°C together with a carrier gas, and carbon nanotubes are generated in a floating state or on the reactor wall, or a catalyst support reaction method is used in which metal-containing particles previously supported on ceramics such as alumina or magnesium oxide are brought into contact with a carbon-containing compound at a high temperature to generate carbon nanotubes on a substrate. For example, carbon nanotubes with an average diameter of 9 nm to 20 nm can be obtained by a catalyst-supported reaction method, and carbon nanotubes thicker than this can be obtained by a suspended flow reaction method. The diameter of the carbon nanotubes can be adjusted, for example, by the size of the metal-containing particles and the reaction time.

[0042] The amount of carbon nanotubes is 0.1 to 3.5 parts by mass per 100 parts by mass of perfluoroelastomer. The amount of carbon nanotubes can be 0.5 to 3.0 parts by mass per 100 parts by mass of perfluoroelastomer. The amount of carbon nanotubes can be adjusted together with the amount of carbon black. If the amount of carbon nanotubes is less than 0.1 parts by mass, the tensile strength and elongation at break at high temperatures are low, and if it exceeds 3.5 parts by mass, the rubber hardness increases and the compression set properties in a high-temperature environment are reduced.

[0043] 2.4. Other compounding agents Bituminous coal pulverized material may be further blended with the perfluoroelastomer. Bituminous coal pulverized material is obtained by pulverizing general coal, including bituminous coal (classified as B1, B2, C in JIS M1002), a type of coal known as high-grade coal, to an average particle size of 1 μm to 100 μm. Furthermore, the average particle size of the pulverized bituminous coal may be 1 μm to 10 μm, and in particular, the average particle size of the pulverized bituminous coal may be 3 μm to 8 μm. The amount of the pulverized bituminous coal may be 1 part by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the perfluoroelastomer. By including 1 part by mass or more of the pulverized bituminous coal, an effect of excellent compression set is obtained, and if included in an amount exceeding 10 parts by mass, the composition tends to become brittle. Bituminous coal Although ground material is sometimes considered to be a type of carbon black, it will be described here as being outside the scope of carbon black.

[0044] The average particle size of crushed bituminous coal is measured and published by the manufacturer when it is commercially available, but it can also be obtained as the arithmetic average by observing the crushed bituminous coal using a scanning electron microscope and measuring the particle diameters of more than 2,000 particles, each considered to be a single particle (basic particle).

[0045] The pulverized bituminous coal may have a specific gravity of 1.6 or less, and may further have a specific gravity of 1.35 or less.

[0046] In addition to the above-mentioned components, the carbon fiber composite material can be used by appropriately adding compounding agents that are generally used in the rubber industry, such as an internal mold release agent, a processing aid, a metal oxide or hydroxide such as zinc oxide, an acid acceptor which is a hydrotalcite compound, and a plasticizer.

[0047] 3. Manufacturing method of carbon fiber composite materials A method for producing a carbon fiber composite material according to one embodiment of the present invention includes a first mixing step of kneading 0.1 to 3.5 parts by mass of carbon nanotubes having an average diameter of 0.7 to 30 nm with 100 parts by mass of perfluoroelastomer before crosslinking to obtain a first mixture, a first thin passing step of feeding the first mixture into an open roll having a roll gap set to more than 0 mm and 0.5 mm or less and a roll temperature set to 0°C to 50°C and thin passing the first mixture to obtain a second mixture, a second mixing step of kneading 15 to 50 parts by mass of carbon black having an average particle diameter of 100 to 300 nm with the second mixture to obtain a third mixture, and a second mixing step of kneading the third mixture with 15 to 50 parts by mass of carbon black having an average particle diameter of 100 to 300 nm. and a second thin-threading step of feeding the mixture into open rolls in which the roll gap is set to more than 0 mm and not more than 0.5 mm and the roll temperature is set to 0°C to 50°C, and thin-threading is performed to obtain a carbon fiber composite material, wherein the carbon fiber composite material has a cross-section having a plurality of continuous structures in which the distance between adjacent carbon nanotubes or the distance between the carbon nanotubes and the carbon black is 100 nm or less, the number of the continuous structures per unit area in the cross-section is 0.80 pcs / μm2 to 3.50 pcs / μm2, and the maximum length of the continuous structures in the cross-section is 10 nm or more and 1000 nm or less.

[0048] The method for producing a carbon fiber composite material according to this embodiment will be described in detail with reference to Fig. 5 to Fig. 9. Fig. 5 to Fig. 9 are schematic diagrams showing the method for producing a carbon fiber composite material by an open roll method according to one embodiment of the present invention. Note that the carbon fiber composite material, raw materials, and blending amounts are as described in 1 and 2 above, and therefore repeated explanations will be omitted.

[0049] As shown in Figures 5 to 9, the first roll 110 and the second roll 120 in the two-roll open roll 100 are arranged with a predetermined roll distance d, for example, 0.5 mm to 1.5 mm, and rotate forward or backward at rotation speeds V1, V2 in the direction indicated by the arrows in Figures 5 to 9.

[0050] First, as shown in Fig. 5, the pre-crosslinked perfluoroelastomer 30 wound around the first roll 110 is masticated to appropriately cut the perfluoroelastomer molecular chains and generate free radicals. The free radicals of the perfluoroelastomer generated by mastication are in a state that easily binds to carbon nanotubes.

[0051] 3.1.First mixing step Next, a first mixing step is carried out as shown in Fig. 6. In the first mixing step, carbon nanotubes 81 (0.1 mass parts) having an average diameter of 0.7 nm or more and 30 nm or less are mixed into a bank 34 of uncrosslinked perfluoroelastomer 30 (100 mass parts) wound around a first roll 110. Parts by mass or more and 3.5 parts by mass or less) of perfluoroelastomer 30 are added and kneaded to obtain a first mixture 36 (FIG. 7). The temperature of perfluoroelastomer 30 in this kneading process can be, for example, 0° C. to 100° C., and can also be 0° C. to 50° C. The first mixing step is not limited to the open roll method, and for example, an internal kneading method or a multi-screw extrusion kneading method can also be used.

[0052] 3.2. First thin-threading process 7, a first thin passing step is performed. In the first thin passing step, the first mixture 36 is fed into open rolls 100 in which the roll gap d is set to more than 0 mm and not more than 0.5 mm and the roll temperature is set to 0° C. to 50° C., and thin passing is performed to obtain a second mixture 37.

[0053] The thin passing can be performed, for example, about 1 to 10 times.

[0054] If the surface speed of the first roll 110 is V1 and the surface speed of the second roll 120 is V2, the surface speed ratio (V1 / V2) between the two during thin passing can be 1.05 to 3.00, and more preferably 1.05 to 1.2. By using such a surface speed ratio, a desired shear force can be obtained.

[0055] The second mixture 37 thus extruded between the narrow rolls is significantly deformed as shown in FIG. 7 by the restoring force due to the elasticity of the perfluoroelastomer, and at that time, the carbon nanotubes move significantly together with the perfluoroelastomer.

[0056] In the first thin-passing process, in order to obtain as high a shear force as possible, the roll temperature is set to a relatively low temperature, for example, from 0°C to 50°C, more preferably from 5°C to 30°C, and the actual measured temperatures of the first mixture 36 and the second mixture 37 can also be adjusted to 0°C to 50°C.

[0057] The shear force thus obtained acts on the perfluoroelastomer, and the aggregated carbon nanotubes are separated from each other and defibrated as if they are pulled out one by one by the perfluoroelastomer molecules, and are dispersed in the perfluoroelastomer. In particular, the perfluoroelastomer has elasticity, viscosity, and chemical interaction with the carbon nanotubes, so that the carbon nanotubes can be easily dispersed. Thus, a second mixture 37 having excellent dispersibility and dispersion stability of the carbon nanotubes (resistance to re-aggregation of the carbon nanotubes) can be obtained.

[0058] More specifically, when perfluoroelastomer and carbon nanotubes are mixed in an open roll, the viscous perfluoroelastomer penetrates into the carbon nanotubes, and a specific part of the perfluoroelastomer bonds with the highly active part of the carbon nanotubes through chemical interaction. If the surface activity of the carbon nanotubes is moderately high, they can be easily bonded to the perfluoroelastomer molecules. Next, when a strong shear force acts on the perfluoroelastomer, the carbon nanotubes also move with the movement of the perfluoroelastomer molecules, and the aggregated carbon nanotubes are separated and dispersed in the perfluoroelastomer by the restoring force of the perfluoroelastomer due to its elasticity after shearing.

[0059] According to this embodiment, when the second mixture 37 is extruded between the narrow rolls, the second mixture 37 is deformed to a thickness greater than the roll gap d due to the restoring force of the elasticity of the perfluoroelastomer. It is presumed that this deformation causes the second mixture 37, which is subjected to a strong shear force, to flow in a more complex manner, dispersing the carbon nanotubes in the perfluoroelastomer. Once dispersed, the carbon nanotubes are prevented from re-aggregating due to chemical interactions with the perfluoroelastomer, and good dispersion stability can be achieved.

[0060] The first thin-passing step is not limited to the open roll method, and an internal kneading method or a multi-screw extrusion kneading method can also be used as long as the carbon nanotubes can be defibrated in the perfluoroelastomer by shear force. In short, this step only requires that a shear force capable of separating and defibrating the aggregated carbon nanotubes can be applied to the perfluoroelastomer. In particular, the open roll method is preferred because it allows not only the roll temperature to be controlled, but also the actual temperature of the mixture to be measured and controlled.

[0061] 3.3.Second mixing process Next, as shown in Fig. 8, a second mixing step is performed. In the second mixing step, carbon black 82 (15 parts by mass or more and 50 parts by mass or less) having an average particle size of 100 nm or more and 300 nm or less is kneaded into the bank 34 of the second mixture 37 wound around the first roll 110 to obtain a third mixture 38 (Fig. 9). Here, the blending amount of carbon black 82 is the blending amount relative to 100 parts by mass of perfluoroelastomer. The processing method and processing conditions of the second mixing step are the same as those of the first mixing step.

[0062] 3.4. Second thin-threading process Next, a second thin passing step is performed as shown in Fig. 9. In the second thin passing step, the third mixture 38 is fed into open rolls 100 in which the roll gap d is set to more than 0 mm and not more than 0.5 mm and the roll temperature is set to 0°C to 50°C, and thin passing is performed to obtain a carbon fiber composite material 50. The processing conditions, such as the number of thin passes and the surface speed, are the same as those in the first thin passing step.

[0063] The carbon fiber composite material 50 obtained by thin-passing may be rolled with a roll to be cut into a sheet of a predetermined thickness. A crosslinking agent can be mixed with the perfluoroelastomer before the first mixing step, during the first mixing step, before the second mixing step, during the second mixing step, or after the second mixing step.

[0064] 3.5.Crosslinking process In the crosslinking step, the perfluoroelastomer in the carbon fiber composite material 50 (FIG. 9) obtained in the second thin-passing step is crosslinked to obtain a carbon fiber composite material. In the crosslinking step, for example, the carbon fiber composite material containing a crosslinking agent is placed in a mold, and the mold is heated to crosslink the perfluoroelastomer and press-process the material to form a rubber product (such as a sealant) of a desired shape using the carbon fiber composite material. As the crosslinking agent, a known peroxide or crosslinking catalyst can be used. In the carbon fiber composite material obtained in the crosslinking step, the above-mentioned continuous structure can be observed in a scanning electron microscope image of the cross section.

[0065] Although the embodiments of the present invention have been described in detail as above, it will be readily apparent to those skilled in the art that many modifications can be made without substantially departing from the novel features and effects of the present invention. Therefore, all such modifications are intended to be included within the scope of the present invention. EXAMPLES

[0066] (1) Preparation of samples The samples of Examples 1 to 7 and Comparative Examples 1 to 8 were produced by the following process.

[0067] Kneading step: 100 parts by mass (phr) of perfluoroelastomer shown in Tables 1 and 2 (shown as "FFKM1" and "FFKM2" in Tables 1 to 3) was put into an open roll with a roll diameter of 6 inches (roll temperature 10°C to 20°C, roll spacing 0.5mm to 1.0mm) and masticated by winding it around the roll (see FIG. 5). The roll temperature in each of the following steps was 10°C to 20°C.

[0068] First mixing step: Next, carbon nanotubes (parts by weight (phr) shown in Tables 1 to 3) (Table The first mixture was obtained by kneading the perfluoroelastomer (see FIG. 6) with the roll gap d set to 1.5 mm.

[0069] First thin-passing step: The first mixture was removed from the rolls, the roll gap d was narrowed from 1.5 mm to 0.3 mm, and the first mixture was fed into an open roll for thin-passing to obtain a second mixture (see FIG. 7). At this time, the surface speed ratio of the two rolls was set to 1.1. Thin-passing was repeated five times. In Comparative Examples 1 and 7, carbon black was fed instead of carbon nanotubes in the first mixing step, and the second mixing step and the second thin-passing step were omitted.

[0070] Second mixing step: Next, with the roll distance d set to 1.5 mm, carbon black (referred to as "HS-CB" and "MT-CB" in Tables 1 to 3) and pulverized bituminous coal (referred to as "Austin Black" in Tables 1 to 3) in the parts by mass (phr) shown in Tables 1 to 3 were added to the second mixture (see FIG. 8), and kneaded to obtain a third mixture.

[0071] Second thin-threading step: The third mixture was taken out from the rolls, and the roll gap d was narrowed from 1.5 mm to 0.3 mm. The third mixture was put into an open roll and thin-threaded to obtain a carbon fiber composite material (see FIG. 9). At this time, the surface speed ratio of the two rolls was set to 1.1. Thin-threading was repeated five times.

[0072] Furthermore, peroxide or a crosslinking catalyst was added as a crosslinking initiator to separate out a carbon fiber composite material before crosslinking having a thickness of 1 mm.

[0073] The separated sheet was placed in an O-ring mold, and molded by press crosslinking and secondary crosslinking to obtain an O-ring of AS568C-214 (hereinafter referred to as "sample"). Here, the samples of Examples 1 to 6 were first crosslinked at 170°C for 24 minutes, and second crosslinked at 300°C (9 hours of temperature rise + 4 hours of holding), while the sample of Example 7 was first crosslinked at 165°C for 10 minutes, and second crosslinked at 290°C (8 hours of temperature rise + 16 hours of holding). Furthermore, the samples of Comparative Examples 1 to 6 were first crosslinked at 170°C for 24 minutes, and second crosslinked at 300°C (9 hours of temperature rise + 4 hours of holding), while the samples of Comparative Examples 7 and 8 were first crosslinked at 165°C for 10 minutes, and second crosslinked at 290°C (8 hours of temperature rise + 16 hours of holding).

[0074] The details of the perfluoroelastomer and various compounding ingredients in the compounding column of the table are as follows:

[0075] FFKM1: Mooney viscosity ML 1+10 121℃ (center value) 80 crosslinking catalyst system, FFKM2: Mooney viscosity ML 1+10 Peroxide crosslinking system at 121℃ (center value) 75 HS-CB: High structure SRF grade carbon black, average particle size 70 nm, DBP absorption (A method) 152 cm 3 / 100g, MT-CB: MT grade carbon black, average particle size 200 nm, Austin Black: Bituminous coal crushed material with an average diameter of 5 μm. MWCNT1: Multi-wall carbon nanotube, average diameter 15.3 nm; MWCNT2: Multi-wall carbon nanotube, average diameter 18 nm, SWCNT: Single-wall carbon nanotube, average diameter 5 nm; It was.

[0076] The carbon black was blended while adjusting the hardness of each sample to be 68 to 82.

[0077] The test samples of Examples 1 to 7 and Comparative Examples 1 to 8 were subjected to various tests described below, and the test results are shown in Tables 1 to 3.

[0078] (2) Basic characteristics test For each sample in the examples and comparative examples, the international rubber hardness (Hs(IRHD)) was measured according to the JIS Measurement was based on K 6253.

[0079] For each sample in the examples and comparative examples, a tensile test was performed in a high temperature atmosphere (260±2°C) at a tensile speed of 500mm / min based on ASTM D1414 using a Shimadzu Autograph AG-X tensile tester, and the tensile strength (TS / 260°C (MPa)), elongation at break (Eb / 260°C (%)), and 25% stress (M25 / 260°C (MPa)) were measured. The measurement results are shown in each column of the table.

[0080] (3) Compression set test For each sample of the examples and comparative examples, the compression set (CS260℃ 70hr, 168hr, 336hr(%)) after holding at 260℃ and a compression ratio of 25% for 70, 168, and 336 hours was measured according to ASTM D395. The measurement results are shown in each column of the table.

[0081] (4) SEM measurement The fracture surface of each sample after the tensile test in the examples and comparative examples was photographed by SEM. The distance between adjacent carbon nanotubes or between the carbon nanotube and the carbon black in each image was measured, and adjacent carbon nanotubes and carbon black with a distance of 100 nm or less were identified as continuous structures, and the number of continuous structures in each image was counted to calculate the number of continuous structures per unit area. The calculation results are shown in Tables 1 to 3. In addition, the maximum length of all continuous structures in each image was measured, and the maximum and minimum values ​​are shown in Tables 1 to 3.

[0082] [Table 1]

[0083] [Table 2]

[0084] [Table 3]

[0085] According to Tables 1 to 3, the samples of Examples 1 to 7 had an international rubber hardness of 74 or more and 81 or less.

[0086] According to Tables 1 to 3, the samples of Examples 1 to 7 had a tensile strength (TS) of 2.5 MPa or more at 260° C. and an elongation at break (Eb) of 65% or more at 260° C. The samples of Comparative Examples 1, 2, and 7 had a tensile strength (TS) of 2.0 MPa or less at 260° C., and the samples of Comparative Examples 1 to 8 had an elongation at break (Eb) of 58% or less at 260° C.

[0087] According to Tables 1 to 3, the samples of Examples 1 to 7 had a compression set of 48% or less when held at 260°C and a compression rate of 25% for 168 hours, while the samples of Comparative Examples 3 to 6 and 8 had a compression set of 53% or more when held at 260°C and a compression rate of 25% for 168 hours.

[0088] According to Tables 1 to 3, the number of continuous structures per unit area of ​​the samples of Examples 1 to 7 was 1.22 / μm 2 ~2.80 pieces / μm 2 The results are shown in Table 1. The number of continuous structures per unit area is 0.76 / μm 2 The results were as follows.

[0089] According to Tables 1 to 3, the maximum length of the continuous structure of the samples of Examples 1 to 7 was 32 μm to 865 μm. The maximum length of the continuous structure of the samples of Comparative Examples 2, 4 to 6, and 8 was 1341 μm or more, and the samples of Comparative Examples 1 and 7 did not have a continuous structure because they did not contain carbon nanotubes. [Explanation of symbols]

[0090] 30...perfluoroelastomer, 34...bank, 36...first mixture, 37...second mixture, 38...third mixture, 50...carbon fiber composite material, 81...carbon nanotubes, 82...carbon black, 84...continuous structure, 90...image, 100...open roll, 110...first roll, 120...second roll, d...roll spacing, L1...distance, L2...maximum length, V1, V2...rotation speed

Claims

1. A carbon fiber composite material containing carbon nanotubes with an average diameter of 0.7 nm to 30 nm and carbon black with an average particle diameter of 100 nm to 300 nm in a crosslinked perfluoroelastomer, the amount of the carbon nanotubes is 0.1 parts by mass or more and 3.5 parts by mass or less based on 100 parts by mass of the perfluoroelastomer, the amount of carbon black is 15 parts by mass or more and 50 parts by mass or less based on 100 parts by mass of the perfluoroelastomer, the carbon fiber composite material has a plurality of continuous structures in which the distance between adjacent carbon nanotubes or the distance between the carbon nanotubes and the carbon black is 100 nm or less in a cross section thereof, The number of the continuous structures per unit area in the cross section is 0.80 / μm 2 ~3.50 pieces / μm 2 and The carbon fiber composite material, wherein the maximum length of the continuous structure in the cross section is 10 nm or more and 1,000 nm or less.

2. In claim 1, The tensile strength measured in accordance with ASTM D1414, except in a 260°C environment, is 2.2 MPa or more, and the elongation at break is 60% or more. A carbon fiber composite material having a compression set of less than 50% after being held at 25% compression at 260° C. for 168 hours as measured in accordance with ASTM D395.

3. In claim 1 or 2, A carbon fiber composite material having an international rubber hardness (IRHD) measured in accordance with JIS K6253 of 68 or more and 82 or less.

4. a first mixing step of kneading 100 parts by mass of a perfluoroelastomer before crosslinking with 0.1 parts by mass to 3.5 parts by mass of carbon nanotubes having an average diameter of 0.7 nm to 30 nm to obtain a first mixture; a first thin passing step of feeding the first mixture into an open roll having a roll gap set to more than 0 mm and 0.5 mm or less and a roll temperature set to 0° C. to 50° C., and thin passing the first mixture to obtain a second mixture; a second mixing step of kneading the second mixture with 15 parts by mass or more and 50 parts by mass or less of carbon black having an average particle size of 100 nm or more and 300 nm or less to obtain a third mixture; a second thin passing step in which the third mixture is fed into an open roll having a roll gap set to more than 0 mm and not more than 0.5 mm and a roll temperature set to 0° C. to 50° C., and thin-passed to obtain a carbon fiber composite material; Including, the carbon fiber composite material has a plurality of continuous structures in which the distance between adjacent carbon nanotubes or the distance between the carbon nanotubes and the carbon black is 100 nm or less in a cross section thereof, The number of the continuous structures per unit area in the cross section is 0.80 / μm 2 ~3.50 pieces / μm 2 and wherein the maximum length of the continuous structure in the cross section is 10 nm or more and 1,000 nm or less.

Citation Information

Patent Citations

  • Over-discharge preventer

    JP1983016474A

  • Paper money identifier

    JP1987084394A

  • Carbon fiber composite material and method for producing the same

    JP2005097525A

  • Method for producing carbon fiber composite material, carbon fiber composite material and oil field apparatus

    JP2012224816A

  • Sealing member and method for producing the same

    JP2013023575A